Pemilihan Supplier Bahan Baku Kain dengan Menggunakan Technique For Others Reference by Similarity to Ideal Solutions (TOPSIS) - Fahra Andiani Sukma; Rakhmat Ceha; Reni Amaranti (Bandung Conference Series: Industrial Engineering Science, 2022)
Abstract. CV. Mawa Heejra is a garment company that manufactures muslim apparel and worship items for both men and women. CV. Mawa Heejra is now facing product delivery delays to customers. This is due to a delay in the supply of raw materials from suppliers, which causes a temporary stop in manufacturing activity. The consequence of halted production activities is that the product completion schedule is incompatible with what was promised and agreed upon with customers. Efforts are being undertaken to solve these issues, namely by selecting suppliers based on CV Mawa Heejra's demands and interests. This technique is known as the Technique for Others Reference by Similarity to Ideal Solutions (TOPSIS). The results obtained are the supplier selection factors used by CV. Mawa Heejra in supplier assessment includes price, material quality, timeliness, delivery quantity accuracy, warranty policy, communication system, professional supplier, attitude, and geographical location. Furthermore, this research generates a recommended standard operating procedure for supplier selection so that the raw material procurement process may be carried out in a more structured manner, reducing the risk of production stoppage due to supplier delivery delays. This research also creates a supplier selection tool in Microsoft Excel to support in the execution of the procedures developed. Abstrak. CV. Mawa Heejra adalah perusahaan garmen yang memproduksi pakaian muslim dan perlengkapan ibadah untuk pria dan wanita. Saat ini CV. Mawa Heejra mengalami permasalahan keterlambatan pengiriman produk kepada konsumen. Hal ini disebabkan oleh keterlambatan kedatangan bahan baku dari pemasok yang menyebabkan kegiatan produksi terhenti untuk sementara. Akibat dari kegiatan produksi yang terhenti yaitu jadwal penyelesaian produk yang tidak sesuai dengan apa yang sudah dijanjikan dan disepakati dengan konsumen. Upaya yang dilakukan untuk mengatasi permasalahan tersebut yaitu dengan melakukan pemilihan pemasok sesuai dengan kebutuhan dan kepentingan CV. Mawa Heejra. Metode yang digunakan adalah Technique for Others Reference by Similarity to Ideal Solutions (TOPSIS). Hasil yang diperoleh yaitu terdapat Sembilan kriteria yang dibutuhkan CV. Mawa Heejra dalam melakukan pemilihan supplier diantaranya harga, kualitas bahan, ketepatan waktu, ketepatan jumlah pengiriman, kebijakan garansi, sistem komunikasi, pemasok yang professional, attitude, dan letak geografis. Selain itu, penelitian ini menghasilkan usulan berupa standar operasional prosedur untuk pemilihan pemasok sehingga proses pengadaan bahan baku dapat dilakukan lebih terstruktur. Pada penelitian ini dibuat rancangan pemilihan pemasok menggunakan Microsoft Excel untuk mempermudah dalam melakukan pemilihan pemasok.